Computational Study Of Static Load on Fem Based Electro-Hydraulic Operating Bed Structure in Solidworks - Ignatius Henry Ismadi; Peter Hagios Asa; Doni Raharjo; Benediktus Indra; Yudha Samodra (Magister Teknik Mesin Universitas Pancasila, 2025)
The electro-hydraulic operating table is a vital component in contemporary surgical systems, responsible for supporting the patient’s body throughout various procedures. Ensuring the structural strength and stability of the bed frame is critical for maintaining patient safety and enhancing procedural success. This study investigates the mechanical performance of key substructures within the bed unit, namely the cranial support structure, dorsal frame, pelvic base, and lower limb support frame. A static structural analysis was conducted using SOLIDWORKS Simulation software, incorporating load distribution data based on a 280 kg patient. Results revealed maximum stress values of 14.888 N/mm² (cranial support), 105.621 N/mm² (dorsal frame), 2.495 N/mm² (pelvic base), and 81.185 N/mm² (lower limb support). All stress values were below the yield strength of aluminum casting (220 N/mm²), indicating structural safety. The findings suggest that the current frame design is mechanically reliable and suitable for clinical deployment under specified load conditions.